Anatomical deviation of male organs of land planarians from Rio de Janeiro, Brazil, with description of two new species of Cratera (Platyhelminthes, Tricladida) - Carbayo, Fernando; Almeida, Ana Laura (Zootaxa, 2015)
Two new land planarian species, collected in the State of Rio de Janeiro, Brazil, are described. Their external aspect is similar to that of Imbira marcusi Carbayo et al., 2013 and Pseudogeoplana theresopolitana (Schirch, 1929), respectively. The analysis of the internal organs, however, revealed they belong to the genus Cratera. The male copulatory organs of one species is very different from any other geoplaninid, for the penis papilla holds a large, distal cavity receiving the ejaculatory duct and, furthermore, the papilla projects vertically downwards from the roof of the male atrium. Thus we consider it as a new species, Cratera cuarassu sp. nov. The second species differs from its congeners in that the dorsal insertion of the penis papilla is anterior to the ventral one, and in that the female atrium is narrowed in the anterior portion. The species was found in the type locality of Pseudogeoplana theresopolitana (Schirch, 1929) and compares well with it in the external features. However, since its internal organs are unknown and the type material of the species is seemingly lost, we describe it as Cratera anamariae Carbayo, sp. nov.